1975
DOI: 10.1172/jci108182
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of contact activation cofactor.

Abstract: A B S T R A C T The contact phase of intrinsic clotting involves Factor XI, Factor XII, Fletcher factor, and a fourth activity that we call contact activation cofactor (CAC). All four of these activities are reduced or absent in Dicalite-adsorbed plasma. A modified activated partial thromboplastin time assay for CAC has been defined by using a substrate of Dicalite-adsorbed plasma combined with partially purified sources of Factors XI and XII, and Fletcher factor. The following properties of CAC in plasma have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 22 publications
(22 reference statements)
2
26
0
Order By: Relevance
“…Whether activated PTA remains attached to a complex is not clear. As far as HMWkininogen is concerned, this is consistent with a previous report (41) that the amount of activated PTA was proportional to the amount of contact activation co-factor (HMW-kininogen) present. Griffin and Cochrane (40) (Table II) and in a purified system (Table III).…”
Section: Discussionsupporting
confidence: 92%
“…Whether activated PTA remains attached to a complex is not clear. As far as HMWkininogen is concerned, this is consistent with a previous report (41) that the amount of activated PTA was proportional to the amount of contact activation co-factor (HMW-kininogen) present. Griffin and Cochrane (40) (Table II) and in a purified system (Table III).…”
Section: Discussionsupporting
confidence: 92%
“…We have recently demonstrated that prekallikrein and HMW kininogen normally circu-late as a complex (15) and proposed that such binding might facilitate the trimolecular interaction that takes place upon the surface. Because the activation of Factor XI, the other Hageman factor substrate, is also augmented by HMW kininogen (10)(11)(12)(13)16), we have examined the possibility that Factor XI forms a complex with HMW kininogen (17). In this paper we show that Factor XI is bound to HMW kininogen in whole plasma and that such binding is also demonstrable utilizing highly purified components.…”
Section: Introductionmentioning
confidence: 91%
“…Kininogens were isolated from normal human plasma at room temperature by modifications of published methods (5,(7)(8)(9)(10). Blood was drawn into silicone-coated vessels containing 0.02 vol of 0.5 M citrate buffer, pH 5.2, hexadimethrine bromide to give a final concentration of50 ,ug/ml and EDTA to give a final concentration of 0.003 M. The plasma was separated during centrifugation at room temperature and made platelet-deficient by recentrifugation.…”
Section: Introductionmentioning
confidence: 99%